THE USE OF ACTION BINGO GAME IN TEACHING VOCABULARY TO ELEMENTARY SCHOOL STUDENTS - Desri Wahyuni; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
This paper talks about the use of Action Bingo game in helping the students of Elementary School Grade 6 in mastering vocabularies related to verbs in English. The writer will explain about the procedures and the advantages of Action Bingo Game. This game could be played individually or in pair. In this game, the teacher distributes one board that has 16 columns in each board, there will be one verb in one column. The teacher mimes every single verb in the board randomly. The students give a mark in the column that consists of verb that has been mimed by the teacher. If a student has marked four squares in a row :horizontally, vertically, or diagonally, they should call out “BINGO!.” The game is over when every column has been marked. This game could make English learning process become more interesting. Furthermore, this game could increase the students’ motivation and ease them in mastering the meanings of vocabularies related to verbs in English.